2018
DOI: 10.3329/seajph.v7i2.38851
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial resistance pattern of uropathogens in a tertiary care hospital in Dhaka city, Bangladesh

Abstract: Urinary tract infection (UTI) is one of the most common bacterial infections seen in developing countries like Bangladesh. This study is, therefore, designed to determine the bacterial uropathogens and their antibiotic resistance pattern among patients with complaints of UTIs in Dhaka city. This study was carried out in the laboratory of the Department of Microbiology, Bangladesh Medical College, Dhaka, Bangladesh from January to June 2015. A total of 2541 urine samples were collected in sterile containers fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
3
9
1
Order By: Relevance
“…In accordance with the several global and national reports our study revealed Escherichia coli (71.5%) as the most predominantly isolated uropathogen associated with UTIs in all age groups [1- 12,13,8]. Throughout the entire study, 30.1% of Escherichia coli isolates showed resistant against Nitrofurantoin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In accordance with the several global and national reports our study revealed Escherichia coli (71.5%) as the most predominantly isolated uropathogen associated with UTIs in all age groups [1- 12,13,8]. Throughout the entire study, 30.1% of Escherichia coli isolates showed resistant against Nitrofurantoin.…”
Section: Discussionsupporting
confidence: 90%
“…The present study of cumulative MIC of Nitrofurantoin resistance have reported high level of resistance on Klebsiella pneumoniae (92.3%), which is in agreement with the findings of few studies from India and Taiwan quoted high resistance against Nitrofurantoin (>75%) in Klebsiella pneumoniae [14,15,16] Interesting thing is that the world seem Nitrofurantoin is sensitive in world for treatment and prophylaxis of Klebsiella pneumoniae in lower UTIs and noscomial infection [1- 13,8,3].…”
Section: Discussionsupporting
confidence: 89%
“…20 Comparable prevalence rate of MDR uropathogens to commonly prescribed antimicrobials has also been reported by some recent studies. 21,22 We found nitrofurantoin and amikacin as better choice except Pseudomonas spp. which is consistent with our previous report and other recent studies.…”
Section: Discussionmentioning
confidence: 88%
“… 20 Comparable prevalence rate of MDR uropathogens to commonly prescribed antimicrobials has also been reported by some recent studies. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Tarana et al [44] reported that Salmonella typhi was found sensitive to amikacin (70%), azithromycin (73%), ceftazidime (63%), ceftriaxone (67%) and ciprofloxacin (87%). Another study (2017) found E. coli in 86% of urine samples collected from a private medical college hospital in Dhaka which was highly resistant to amoxicillin (95%) [45]. More than 80% of MRSA isolates are also found to be sensitive to some macrolides (tobramycin, gentamycin) and carbapenem (meropenem) with resistant to ampicillin, amoxicillin, cefixime and azithromycin [46].…”
Section: A1ntimicrobialmentioning
confidence: 99%